SCHOOL LIBRARY AS AN IQRO’ CENTER FOR PRIMARY STATE OF STUDENTS - Nuridin Nuridin; Hanik Mas Unah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2018)
Library is an important element in supporting the success of learning activities. Therefore library management should be maximized. The function of the library in general is as a source of learning because in there available various library materials, but the problem is a lot of libraries especially library school of primary school (SD) which management is less than the maximum. Source of data in this research were principal, librarian, teacher, and student. Data collection techniques through observation, interview and documentation. Data analysis was used the method of reduction and tested with the test credibility.  This study aims to determine the various obstacles and efforts that make the school library as Iqro’ Center for students primary state of Bangetayu Wetan 02. Iqro' Center is the concept of Islamic library which aims to make the library as a center of student activities in reading and discussion according to QS. Al-'Alaq verses 1-5. The results showed that the biggest obstacle of this library is the absence of librarians so that circulation services are not running. These constraints can be overcome by fulfillment of librarians. In accordance with the results of interviews, to make the school library as Iqro’ Center for business students that need to do is to adjust the library materials to the needs of students, as well as the need for motivation from teachers to build reading interest in students. Therefore, in managing the library should involve teachers and students because they are the library users.